La inexistencia de normatividad, que regule la verificación real de que se perciban alimentos y otros elementos de manutención por parte del obligado hacia el derecho habiente en el código de la niñez y la adolescencia genera en el mal uso del derecho a alimentos. - Luzuriaga Alvarado, José Paúl (2011)
It is verified if really the child support Money is used exclusively in the beneficiary, so it has to regulate this situation in the Organic Code of Chilhood and adolescence. It provides some conclusions, recommendations and gives an alternative of solution that is the legal proposal of reform. But the big problem facing the child, adolescent, or any other beneficiary of the Right to Food, which is not proven in a real way to receive food and other support required by the holder to the right, is leaving calamity in the field of health, in the legal field and in the social area, with regard to health the lack of nutrients in the human body carries physiological alterations such as delay in physical, psychological and intellectual development, to subsequently pass to a very sad field of diseases such as anemia, caused by a bad and almost nonexistent nourishment, now in the legal area this problem has even more connotation due to unless is proved that in fact the alimony money is used in food for child, is being promoted legal uncertainty for a subject of rights such as the child or adolescent and since if this money is given, is to do just that to deliver food and other child support, that is the main purpose of the special legislation of childhood and adolescence in the area of Right to Food, therefore is assembled a whole super state structure like the courts that try to provide justice in the range of childhood and adolescence, specialized police for childhood and adolescence, the constitutional mandate of imprisonment for debt of alimonies, building a amounts table of alimonies made by the National Council for Childhood and Adolescence, all that is going to the ground because there is not a real verification that are received food and other support required by the holder to the right of the Organic Code of Childhood and Adolescence which causes the misuse of Right to Food. Second, sponsoring the principles of children rights, such as the Right to Food principle, is not being respected at all even, is made a table of the nutrition right that children have, for this unfortunate situation that is giving in substantive right of Ecuador in childhood and adolescence area, which motivated me to carry out this study, in order to provide complete protection to the Right to Food of children, is very important to change this harmful situation in the Organic Code of Childhood and Adolescence, since the Right to Food is a basic human right for the prolongation and development of life, to carry out the Right to Food for the child is necessary and analyzing this problem of the not checking the destination of the alimony money, extends a little more the effects of these problems and above all gives a hint of solution, with the only purpose of this Right to Food materializes for children, adolescents, and any other beneficiary to one hundred percent. Now in the social area, I see that is being fulfilled this popular adage that states it is so easy like taking candy from a baby (emphasis are mine) they are doing just that, they are taking the most defenseless beings of the world society their food, health, hope, happiness. It produces frightening to think that there are people who wasted alimony money on issues completely unrelated to the child's interest, but there those people and they are enough, those are entrusted by possession or custody of the children, adolescent or any other beneficiary who does not manage properly his money for alimony; society is attentive, apparently it is passive, but constantly working on the most vulnerable of the social body, as when the Lions Club of Loja, delivers educational equipment for children of our community is evidence that society is aware of our children, and those bad managers of money they receive for alimony are morally sanctioned like irresponsible, unscrupulous to other positive entities of social body, lacking only a legal sanction be imposed.